KOMUNIKASI PARIWISATA POKDARWIS DALAM MEMBENTUK DESTINATION BRANDING DESA WISATA ALAHAN PANJANG DANAU DIATAS KABUPATEN SOLOK - ', Karina; Yozani, Ringgo Eldapi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2024)
Alahan Panjang Danau Diatas Tourism Village is a tourist destination in Solok Regency that has great potential for development in improving the tourism sector. Pokdarwis plays an important role in mobilizing local communities to develop the potential of their area through cooperation with the government and other external parties to attract tourists to visit. The purpose of this study is to analyze Pokdarwis tourism communication through the potential of the 3A tourism components and strategies for forming destination branding. The research method uses a descriptive-qualitative approach with the selection of informants through purposive techniques. Data collection techniques include interviews, observations, and documentation, which are analyzed through interactive models, namely reduction, data presentation, and conclusion drawing, which then use triangulation techniques to test the validity of the data. The results showed that Pokdarwis tourism communication through the 3A component is natural beauty, tourism products become attractions offered, accessibility is easy to reach, and amenity is quite complete and good. The destination branding strategy carried out by Pokdarwis is through market investigation, analysis, and recommendation; brand identity development; brand launch; brand implementation; and monitoring, evaluation, and review. Keywords: Tourism Communication, Destination Branding, 3A Tourism Components, Tourism Village, Pokdarwis